2012
DOI: 10.1063/1.3684750
|View full text |Cite
|
Sign up to set email alerts
|

The final stages of capillary break-up of polymer solutions

Abstract: The capillary break-up of a polymer solution evolves via a series of stages. After the initial instability a long-lived cylindrical filament is formed, which thins exponentially in time, while the flow is purely extensional. During the final stages of the thinning process, at which the polymers are stretched sufficiently for the filament to become unstable to a Rayleigh-Plateau-like instability, a complex flow pattern develops, which we describe here. Achieving a high spatial resolution well below the optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 29 publications
11
109
0
1
Order By: Relevance
“…The formation of a 'skin' of coagulated polymer occurs on first contact between a polymer jet filament and the coagulation bath [13]. The 'skin' clearly prevents the fiber from breaking up into spherical drops due to PlateauRayleigh instability [14]. This instability usually appears in the electrospinning of extremely dilute polymer solutions, where the resultant droplet formations are described as a 'pearl effect' on the fibers, 'beads-on-a-string', or simply as 'polymer beads' [15].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a 'skin' of coagulated polymer occurs on first contact between a polymer jet filament and the coagulation bath [13]. The 'skin' clearly prevents the fiber from breaking up into spherical drops due to PlateauRayleigh instability [14]. This instability usually appears in the electrospinning of extremely dilute polymer solutions, where the resultant droplet formations are described as a 'pearl effect' on the fibers, 'beads-on-a-string', or simply as 'polymer beads' [15].…”
Section: Introductionmentioning
confidence: 99%
“…Its physical properties under elongation are reported in several publications [13,15]. Figure 3 shows the evolution of the fluid capillary bridge.…”
Section: Methodsmentioning
confidence: 99%
“…[13,14,15] some of the authors of the present studies have shown that in extensional rheometry experiments one can resolve the amplitude of the sinusoidal deformation of the cylindrical liquid filament down to a resolution of 80 nm. This could be achieved by fitting the interface profile that was determined by a simple threshold algorithm with a sinus function, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, several criteria have been suggested for the possibility of such flow instability, including extensibility parameters for polymer chains and dimensionless numbers. This phenomenon has been reported experimentally for a flexible polymer such as PEO (Arnolds et al 2010;Oliveira and McKinley 2005;Oliveira et al 2006;Sattler et al 2008), emulsions (Erni et al 2009), human saliva (Sattler et al 2012), and for the systems with rigid polymers such as xanthan gum solution drop falling under gravity (Smolka and Belmonte 2006) and DNA suspensions (Juarez and Arratia 2011).…”
Section: Introductionmentioning
confidence: 98%